In Vitro and In Vivo Comparison of Selected Ga-68 and Zr-89 Labelled Siderophores - Petrik, Milos; Zhai, Chuangyan; Novy, Zbynek; Urbanek, Lubor; Haas, Hubertus; Decristoforo, Clemens (Molecular imaging and biology, 2016)
PURPOSE: Some [(68)Ga]siderophores show promise in specific and sensitive imaging of infection. Here, we compare the in vitro and in vivo behaviour of selected Ga-68 and Zr-89 labelled siderophores. PROCEDURES: Radiolabelling was performed in HEPES or sodium acetate buffer systems. Radiochemical purity of labelled siderophores was determined using chromatography. Partition coefficients, in vitro stability and protein binding affinities were determined. Ex vivo biodistribution and animal imaging was studied in mice. RESULTS: Certain differences among studied siderophores were observed in labelling efficiency. Protein binding and stability tests showed highest stabilities and lowest protein binding affinities for Ga-68 and [(89)Zr]triacetylfusarinine C (TAFC). All studied Ga-68 and [(89)Zr]siderophores exhibited a similar biodistribution and pharmacokinetics in mice with the exception of [(89)Zr]ferrioxamine E (FOXE). CONCLUSIONS: Zr-89 and [(68)Ga]siderophores showed analogous in vitro and in vivo behaviour. Tested [(89)Zr]siderophores could be applied for longitudinal positron emission tomography (PET) studies of fungal infections and especially TAFC for the development of novel bioconjugates.
Keywords: radionuklidy; tkáňová distribuce; počítačová rentgenová tomografie; Tissue Distribution; radioizotopy galia; Positron-Emission Tomography; pozitronová emisní tomografie; myši inbrední BALB C; PET; Zirconium-89; Mice, Inbred BALB C; Zirconium; siderofory; Tomography, X-Ray Computed; Animals; ženské pohlaví; Gallium Radioisotopes; Gallium-68; zvířata; Radioisotopes; Imaging; zirkonium; Siderophores; Female